2009
DOI: 10.3832/ifor0510-002
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients (N, P and K) dynamics associated with the leaf litter of two agroforestry tree species of Bangladesh

Abstract: © iForest -Biogeosciences and Forestry IntroductionChemical fertilizer is now commonly used in agricultural practices, but it becomes ex pensive and farmers are reducing its use due to negative environmental impacts (Good et al. 2004). In addition, access to fertilizer in developing nations is limited (Sanchez 2002). It is an important task to gain a better understanding how agricultural practices can be designed with low input of fertilizer. Maintenance of soil productivity is a critical issue in a tropical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in nutrients (N, P, and K) concentration in the leaf litter of the studied species at the initial stages of decomposition was found (Figures 3, 4, and 5) as the selected tree species were from different families having variation in chemical and biochemical properties of leaf litter [43][44][45]. Comparatively higher initial concentration of N, P, and K concentration in the leaf litter of Z. jujuba indicated that capabilities of this species to retranslocate these nutrients were lower during the senescence of leaves [6,46,47].…”
Section: Nutrients At Different Stages Of Microbial Decompositionmentioning
confidence: 99%
“…In contrast, the PSM activity was favored at the preserved site. According to previous reports (Mahmood et al 2009), E. camaldulensis ensured the supply of phosphorous to the agroforestry system by favoring AMF and PSF activities, as determined by the AMF root colonization and the phosphatase activity, respectively. Finally, these microbial populations may be indicators of soil quality useful in assessing the effectiveness of land restoration in semiarid environments.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 81%
“…It is known that E. camaldulensis litter has a faster decomposition rate (Mahmood et al 2009). In this study, the Eucalyptus litter at the experimental site decomposed faster than the mixture, whereas the P. reticulata litter alone showed the slowest decay, which is likely due to the low lignin content of the former and the high lignin content of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation